Influence of content knowledge and teachers’ attitudes towards the teacher’s readiness of teaching secondary schools quantum physics in Sabah - Stephanie Sungkim (2013)
Due to its importance in today's technological context, quantum physics has been added to the secondary school curriculum in various countries before it was introduced in Malaysia. Since quantum physics has been taught to secondary school students beginning in 2021, therefore this research aimed to determine the level of content knowledge, attitudes, and teacher readiness among physics teachers in secondary schools and to what extent the content knowledge and attitude influence teacher readiness to teach quantum physics in secondary school. This study included all secondary schools in 24 districts across six zones in Sabah. The study was conducted on 175 physics teachers using a quantitative design and a questionnaire method. Data were collected using 41 items modified and adapted questionnaires from previous studies, as well as DSKP Physics KPM. Data collected were analyzed using the IBM Statistical Package for Social Science (SPSS) Version 28.0 for descriptive and inferential statistics. The study's findings revealed that teacher content knowledge and readiness were at a moderate level, while their attitude was at a high level. There is a significant relationship between content knowledge and attitude and teacher readiness with r =.66. This study found that content knowledge is not the predictor of teacher readiness to teach quantum physics to secondary school students. However, attitude contributes 35.7% to teacher readiness compared to content knowledge. Thus, this study found that attitudes are the main predictor of teacher readiness to teach quantum physics among secondary school physics teachers. This study has also revealed the extent that they are ready to introduce quantum physics topics into the classroom in terms of their content knowledge and attitudes. Therefore, the findings of this study enable physics teachers to understand their respective roles and duties better and improve their content knowledge and attitudes, allowing for effective implementation of quantum physics topic teaching.